Pengaruh Earning Per Share Dan Dividend Per Share Terhadap Harga Saham Pada PT. BFI Finance Indonesia Tbk. - Sartika (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2025)
This study aims to determine the effect of Earning Per Share and Dividend Per Share on Stock Prices at PT. BFI Finance Indonesia, Tbk. The types of data used in this study are quantitative data and qualitative data. The analysis method used is descriptive analysis and multiple linear regression, coefficient of determination, correlation coefficient, and F test T test. Regression Calculation Results Y = 1,876 + 1,207X1 – 0,12X2 coefficient of determination R2 = 92,6% correlation coefficient r = 0,962, thus it can be concluded that Earning Per Share and Dividend Per Share have no significant effect on Stock Prices, Partially Earning Per Share has a positive and significant effect on stock prices, and Dividend Per Share has a negative and insignificant effect on Stock Prices at PT. BFI Finance Indonesia, Tbk, thus the H1 and H3 are rejected and H2 is accepted.